Unregistered Divorce among Islamic Boarding School Alumni - Muala, Asyharul; Wahyuni, Sri (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
Divorce does not require a formal court process in Islam; a verbal statement from the husband is considered sufficient. This understanding is held by several Islamic boarding school alumni living in Mlangi, who choose to divorce outside of court. However, this choice is not supported by religious leaders, kiai and gus, who recommend legally divorcing in court to address issues such as inheritance division and child custody. Despite this, Islamic boarding school alumni in Mlangi continue to opt for divorcing outside of court for various reasons. This research aims to investigate the motivations of individuals in Mlangi who choose to divorce outside of the court system, utilizing the Rational Choice Theory as analytical frameworks. Through qualitative methods, the research explores the relationship between religious beliefs, social norms, and individual experiences in out-of-court divorces. The article argues that social institutions like kiai and gus are important figures and serve as places of consultation. However, Islamic boarding school alumni often follow their own interests instead of the advice given. Despite gus and kiai not recommending divorce outside of court, alumni still do so because they want to. This creates a social dilemma where alumni must choose between following norms and pursuing their interests. The research shows that alumni seek advice from kiai and gus mainly to legitimize their decision to divorce outside of court. The main reasons for divorcing outside of court are privacy issues, lack of communication, a selfish partner, lack of control over the partner, and the absence of children. [Perceraian tidak memerlukan proses pengadilan formal dalam Islam; pernyataan lisan dari suami dianggap cukup. Pemahaman tersebut dianut oleh beberapa alumni pesantren yang tinggal di Mlangi, yang memilih bercerai di luar pengadilan. Namun pilihan tersebut tidak didukung oleh para pemuka agama, kiai dan gus, yang merekomendasikan perceraian secara sah di pengadilan untuk mengatasi permasalahan seperti pembagian warisan dan hak asuh anak. Meski begitu, alumni pesantren di Mlangi tetap memilih bercerai di luar pengadilan karena berbagai alasan. Penelitian ini bertujuan untuk mengetahui motivasi individu di Mlangi yang memilih bercerai di luar sistem pengadilan, dengan perspektif teori pilihan rasional. Penelitian ini mengeksplorasi hubungan antara keyakinan agama, norma sosial, dan pengalaman individu dalam perceraian di luar pengadilan. Pasal tersebut berpendapat bahwa lembaga social, seperti kiai dan gus, yang merupakan tokoh penting dan berfungsi sebagai tempat konsultasi. Namun seringkali para alumni pesantren hanya mementingkan kepentingannya sendiri dibandingkan nasehat yang diberikan. Meski gus dan kiai tidak menganjurkan perceraian di luar pengadilan, namun para alumni tetap melakukannya karena ingin. Hal ini menimbulkan dilema sosial dimana alumni harus memilih antara mengikuti norma atau mengejar kepentingannya. Hasil penelitian menunjukkan bahwa alumni meminta nasihat kepada kiai dan gus terutama untuk melegitimasi keputusan mereka untuk bercerai di luar pengadilan. Alasan utama perceraian di luar pengadilan adalah masalah privasi, kurangnya komunikasi, pasangan yang egois, kurangnya kontrol terhadap pasangan, dan tidak memiliki momongan.]